Patterns of Iberian honey bee variation inferred from the coding regions of whole mtDNA genomes: comparison with the popular intergenic tRNAleu-cox2 region - Pinto, M. Alice (2016)
Iberian honey bees (Apis mellifera iberiensis) are well-known for their complex patterns of variation, which have been extensively reported by PCR-RFLP data of the intergenic tRNAleu-cox2 region of the mitochondrial DNA. This mtDNA marker has revealed a highly structured and diverse subspecies characterized by the presence of western European (M) and African (A) haplotypes belonging to three African sublineages (AI, AII, AIII) forming a cline possibly originated from secondary contact. While the African-derived haplotypes occur in the southwestern half of Iberia, with sublineage AIII mostly present in the northern Atlantic coast, the northeastern half of Iberia is occupied by haplotypes of M ancestry. Here we report on the diversity patterns inferred from the coding portion of 87 mitochondrial whole genomes of Iberian honey bees and 20 of two reference subspecies: the North African A. m. intermissa and the western European A. m. mellifera. The whole mtDNA patterns were compared with those obtained with the intergenic tRNAleu-cox2 region. As expected, a concordant northeastern-southwestern cline formed by the two highly divergent lineages A and M was observed. However, the previously grouping of haplotypes into the three African sublineages is not supported by the entire coding portion of the mitochondrial molecule. This finding suggests that the tRNAleu-cox2 region is still a good marker for understanding the big picture of variation patterns.